The Constitutional Embodiment for Protecting the Public Locations in the Iraqi Republic Constitution Operative for Year 2005 - Zogair Atia, A.M.D. Ganie; Al-Khakany , Mohamed All Mohamed (International Journal of Psychosocial Rehabilitation, 2019)
The Public areas in Iraq enjoyed important constitutional protection because these public areas are considered as Public National Possessions or that they are owned by the government but they are all used directly by all citizens or that they are considered as public utilities for the country.